2021
DOI: 10.1088/1755-1315/662/1/012002
|View full text |Cite
|
Sign up to set email alerts
|

Consumption and Preference of Tropical Vegetables in the Special Region of Yogyakarta

Abstract: Tropical vegetables are essential food sources for health. However, the consumption of vegetables in the Special Region of Yogyakarta is yet relatively low. Meanwhile, the Special Region of Yogyakarta has the potential to supply vegetable commodities. The research objective is to determine the consumption and consumer preference of the attributes of tropical vegetables. The sample of research locations were purposively selected, i.e., Colombo Market, Kranggan Market, Niten Market, Playen Market, Mirota Kampus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…The utility value of consumer preferences was more interested in buying fresh tomatoes. This was consistent with the research finding which confirmed that freshness is an important attribute of the perceived quality of a product (Tsiros & Heilman, 2005;Farruggia, Crescimanno, Galati, & Tinervia, 2016;Hardyastuti & Perwitasari, 2021). Tomatoes were classified as agricultural products, and the characteristics of agricultural products were always synonymous with freshness.…”
Section: Consumers' Preferencesupporting
confidence: 91%
See 3 more Smart Citations
“…The utility value of consumer preferences was more interested in buying fresh tomatoes. This was consistent with the research finding which confirmed that freshness is an important attribute of the perceived quality of a product (Tsiros & Heilman, 2005;Farruggia, Crescimanno, Galati, & Tinervia, 2016;Hardyastuti & Perwitasari, 2021). Tomatoes were classified as agricultural products, and the characteristics of agricultural products were always synonymous with freshness.…”
Section: Consumers' Preferencesupporting
confidence: 91%
“…The analysis is used to model consumer preferences based on consumer perceptions of various product attributes, beginning with determining the attributes and attribute levels (Firdaus, 2011). Attributes are selected based on attributes that have positive values from the results of Fishbein's Multi-attribute analysis and supporting studies, including freshness (Hardyastuti & Perwitasari, 2021), color (Oltman et al, 2014;Adegbola et al, 2019), texture (Usse et al, 2010), fruit surface appearance (Lombart et al, 2019), and taste (Oltman et al, 2014). Some selected attributes had not been specifically capable of representing consumer preferences, so it was necessary to extend the level for each attribute.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations